Extraccion de fenoles y polifenoles en corteza de Eucaliptos - Orea Igarza, U.=700 1 Carballo Abreu, L.R.; Cordero Machado, E.; Perez Diaz, N.
(Es, En)
Ilus., 18 ref.
Keywords: EUCALYPTUS; COMPUESTOS FENOLICOS; POLIFENILOS; CORTEZA; CUBA; EXTRACCION DE FENOLES; REVISTA FORESTAL BARACOA